Volumetric modulated arc therapy versus step‐and‐shoot intensity modulated radiation therapy in the treatment of large nerve perineural spread to the skull base: a comparative dosimetric planning study. Issue 2 (14th April 2014) - Gorayski, Peter; Fitzgerald, Rhys; Barry, Tamara; Burmeister, Elizabeth; Foote, Matthew
Abstract Introduction Cutaneous squamous cell carcinoma with large nerve perineural (LNPN) infiltration of the base of skull is a radiotherapeutic challenge given the complex target volumes to nearby organs at risk (OAR). A comparative planning study was undertaken to evaluate dosimetric differences between volumetric modulated arc therapy (VMAT) versus intensity modulated radiation therapy (IMRT) in the treatment of LNPN. Methods Five consecutive patients previously treated with IMRT for LNPN were selected. VMAT plans were generated for each case using the same planning target volumes (PTV), dose prescriptions and OAR constraints as IMRT. Comparative parameters used to assess target volume coverage, conformity and homogeneity included V95 of the PTV (volume encompassed by the 95% isodose), conformity index (CI) and homogeneity index (HI). In addition, OAR maximum point doses, V20, V30, non‐target tissue (NTT) point max doses, NTT volume above reference dose, monitor units (MU) were compared. Results IMRT and VMAT plans generated were comparable for CI (P = 0.12) and HI (P = 0.89). VMAT plans achieved better V95 (P = < 0.001) and reduced V20 and V30 by 652 cubic centimetres (cc) (28.5%) and 425.7 cc (29.1%), respectively. VMAT increased MU delivered by 18% without a corresponding increase in NTT dose. Conclusion Compared with IMRT plans for LNPN, VMAT achieved comparable HI and CI.